2009
DOI: 10.1097/mcg.0b013e31815b9d11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Diagnostic Value of Duodenal Bulb Histology in Patients With Celiac Disease, Using Multiple Biopsy Sites

Abstract: The biopsies from the duodenal bulb and second part of the duodenum in CD can be equally representative of the underlying disease. The diagnosis of CD can reliably be made even if biopsies are taken from the duodenal bulb rather than distal duodenum or jejunum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 20 publications
0
33
0
1
Order By: Relevance
“…Studies in both children and adults with increased endomysial antibody or tissue transglutaminase antibody titers have also confirmed the patchy nature of villous atrophy and the value of duodenal bulb biopsies to increase the diagnostic yield of celiac disease. [8][9][10][11][12][13][14] Multiple duodenal biopsy samples, including those taken from the duodenal bulb, were recently recommended by a group of investigators who found that celiac disease in children is not only patchy throughout the duodenum, but there can also be significant variability in the severity of the disease in a single biopsy sample. 15 In our study, fewer biopsy samples were taken from the bulb than from the descending duodenum, and this led to a high rate of inadequate diagnostic interpretations of the bulb biopsy samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in both children and adults with increased endomysial antibody or tissue transglutaminase antibody titers have also confirmed the patchy nature of villous atrophy and the value of duodenal bulb biopsies to increase the diagnostic yield of celiac disease. [8][9][10][11][12][13][14] Multiple duodenal biopsy samples, including those taken from the duodenal bulb, were recently recommended by a group of investigators who found that celiac disease in children is not only patchy throughout the duodenum, but there can also be significant variability in the severity of the disease in a single biopsy sample. 15 In our study, fewer biopsy samples were taken from the bulb than from the descending duodenum, and this led to a high rate of inadequate diagnostic interpretations of the bulb biopsy samples.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, several recent studies demonstrated the patchy nature of villous atrophy, with changes restricted to the duodenal bulb in some patients. [6][7][8][9][10][11] A limitation of these studies has been the lack of adequate control groups and a lack of direct comparison of the histologic findings in both the descending duodenum and duodenal bulb.…”
mentioning
confidence: 98%
“…Second, the classical histological lesions may not always be abundant as the development of CD is a dynamic process that often begins with minor changes that can easily be overlooked [13][14][15][16]. Also, the variability in expression of the histological lesions in CD may make diagnostic interpretation more difficult [17,18]. Finally, it should be kept in mind that, especially in children, small bowel mucosal atrophy can also be associated with other diseases that are sometimes difficult to differentiate from CD [19].…”
Section: Introductionmentioning
confidence: 99%
“…Other pediatric studies have not shown an advantage for duodenal bulb biopsies. 16,17 Critique of the present study notwithstanding, it is evident that we do have a problem: there is a subset of patients in whom neither the diagnosis of celiac disease nor its absence is clear-cut. The assertion that patients have celiac disease based on only a Marsh 3 lesion 3 of necessity means that patients with lesser findings likely do not have celiac disease.…”
mentioning
confidence: 88%